2017
DOI: 10.18869/nrip.jamsat.3.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Possible Molecular Mechanisms for Paramecium Learning

Abstract: Learning is a cornerstone of intelligent behavior in animals. This behavior has been mostly studied in organisms with a fairly complex nervous system. However, recent reports of learning in unicellular organisms suggested the existence of associative learning in unicellular organisms. In particular, the capability to associate different light intensities with cathodal stimulation in paramecium is of special interest. We have investigated the previous reports on this phenomenon and proposed a molecular mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Accordingly, the present study made a distinction between dark-cathode and lightcathode association and found that the learning happens only in light-cathode conditions. The theoretical aspects of this issue will be addressed further in this section (using our previous hypothesis (10) on learning mechanisms of paramecium. Particularly, it seems that the data for the control group in Armus et al report might be unreliable (see Figure 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the present study made a distinction between dark-cathode and lightcathode association and found that the learning happens only in light-cathode conditions. The theoretical aspects of this issue will be addressed further in this section (using our previous hypothesis (10) on learning mechanisms of paramecium. Particularly, it seems that the data for the control group in Armus et al report might be unreliable (see Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…However, the molecular mechanism for this process is still unknown. We have previously suggested a molecular model (10) to explain this behavior based on molecular pathways that link cAMP concentration to the phototactic behavior of paramecium. However, our model predicted that paramecium cannot learn to associate lower light intensities (the dark side) with cathodal shocks.…”
Section: Introductionmentioning
confidence: 99%
“…We cannot explain precisely how this agent disrupts learning in Paramecium . It may be explained based on the previously proposed model ( Alipour et al, 2017 ), where learning in Paramecium includes three main processes: a) light detection and phototaxis, b) disruption of phototaxis through electrical stimulation, and c) stimulation aftereffects. Some aspects of this model will be discussed in the following.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that learning in P. caudatum can be impaired upon the administration of a GABA receptor partial allosteric modulator, however, not by disrupting the microtubular dynamics. We cannot explain exactly how this agent disrupts learning in paramecium, but perhaps it may be explained based on the previously proposed model [29], where learning in paramecium includes three main processes: a) light detection and phototaxis, b) disruption of phototaxis through electrical stimulation, and c) stimulation aftereffects.…”
Section: Learning In Paramecium; Phototaxis Effects and Aftereffectsmentioning
confidence: 91%